PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERORIENTASI PENDIDIKAN KARAKTER DENGAN PENDEKATAN GUIDED DISCOVERY PADA MATERI JARINGAN HEWAN UNTUK SMA/MA - Shinta, Mardha; Lufri, Lufri; Razak, Abdul (Kolaboratif, 2013)
The function and purpose of national education is not only to develop the academic skills, but also to form the characterized generation in the future. To realize these it is important develop learning instruments that can support students' character development. So far, teachers are not able to develop learning instruments in accordance with the criteria and conditions of the school and students. This research has purpose to develop the learning instrument of Biology-with character and guided discovery approach for teaching material and worksheet on animal tissue materials for grade XI Science SMA / MA that are valid, practical, and effective. Learning instruments was developed by using a four-D models. Data collection was done by the validation and testing for the instrument that be develope. The design of the instrument that has been designed, validated by three experts and practitioners then tested on a limited basis in the Class XI IPA MA Kampar Timur to know the practicalities and effectiveness of the instruments had been developed. From the results of research conducted in mind that includes lesson plans, Teaching Material and worksheets are on valid category. Based on limited testing, known to its appropriateness in the category of good. The response of teachers and students after using this learning instruments showed positive results with an average response is valid. Observations of student activity enough. Assessment of the cognitive, affective, and psychomotor indicate mastery beyond the minimum. Conclusion of research is the study of biology-oriented character education with guided discovery approach to animal tissue materials for class XI Science SMA / MA is valid, practical, and effective.